Linkages between Sectoral Output Growth and Financial Development in Nepal - Westermann, Frank (NRB Economic Review, 2012)
A feature of the recent period of output growth in Nepal is that growth has been uneven across sectors. While the services sector has been expanding, the agricultural and manufacturing sectors have growing much more slowly. In this paper we attempt to explain this fact by investigating the linkages between financial development and sectoral output growth in a vector-autoregression (VAR) analysis. We find that the services sector reacts strongly to increases in domestic credit, while agriculture and manufacturing are largely unaffected. We interpret this finding in the context of a two sector-growth model, by Schneider and Tornell (2004), where credit constraints and the access to international capital markets play a central role. We also discuss the importance of our findings for the goal of poverty alleviation.